Targeted delivery of boronic acids through bioconjugation - Lopes, Ricardo M. R. M. (2022)
In oncology, a predicament becomes apparent when considering the shared nature of a tumor and healthy tissue. Traditional chemotherapy employs potent cytotoxic small molecules with reasonable selectivity for rapidly-dividing cells. However, the exact biological targets exist in non-malignant tissues. Consequently, most of the cancer chemotherapies in the clinic coexist with severe side effects that reduce the quality of life of their patients. Targeted therapy directly answers traditional chemotherapy’s shortcomings as it targets proteins that control how specific cancer cells grow, divide, and spread. Antibody-drug conjugates are a class of targeted therapeutics, the product of conjugation between a cytotoxic drug and an antibody. These benefit from stable but reversible ligations to release the cytotoxic entities selectively into cancer cells. Boronic acids are a class of biocompatible reagents that can form reversible covalent ligations in water, leading to their successful application in developing stimulus-responsive bioconjugates for targeted therapy. Among these, iminoboronates represent a unique chemical function for protein modification via imine formation between 2-carbonyl benzene boronic acids and lysines. The major innovation of this ligation is the formation of a dative bond between the imine’s nitrogen and the boron atom, which conveys additional stability. However, iminoboronates still display insufficient physiological stability for their use in therapeutic bioconjugates. In this thesis, we developed ligands for iminoboronate formation with improved physiological stability and used them as pH-sensitive linkers in bioconjugates such as peptide-drug conjugate. For that purpose, N,O-bidentate ligands were designed to establish a second point of coordination between the boron atom and the oxygen atom from this ligand, providing additional hydrolytic stability. We proved that 2-methylaminophenol promotes the formation of such coordination with 2-acetylbenzene boronic acid, forming more stable N,O-iminoboronates. These revealed to be still reversible in acid conditions and were used to selectively deliver a “turn-on” fluorogenic payload into cancer cells’ acidic environment mediated by folate receptors. In the following chapter, we applied the same technology to deliver the cytotoxic drug SN-38, which required a structural adaptation to fit the N,O-topology. The SN-38 N,O-iminoboronate was used to produce two peptide bioconjugates. However, the modifications to the core structure of these N,O-iminoboronates, rendered unstable conjugates precluding in bioassay conditions. For that reason, self-immolative chemistry was used to develop a better alternative that is compatible with a more extensive range of payloads. During these studies, we found that boron’s second hydroxyl group from the N,O-iminoboronate could be substituted by other alcohols. We investigated the possibilities that such an additional coordination point could bring to the platform. In summary, the additional coordination of alcohols to the N,O-iminoboronates dramatically stabilizes the whole conjugate until irreversibility, depending on the alcohol used (N,O,O-iminoboronate esters). Finally, by using another modality of iminoboronates, named the B-complexes, we developed synthetic routes to construct dual self-immolative drug conjugates for target therapy.